La estructura familiar y su incidencia en el desarrollo emocional de los niños y niñas del primer grado de educación general básica de la unidad educativa anexa a la Universidad Nacional de Loja, de la ciudad de Loja, periodo lectivo 2013 – 2014. Lineamientos propositivos - Pineda Rojas, Vanessa Romina (2014)
This research thesis is prepared in accordance with the regulations of the National University of Loja whose theme is FAMILY STRUCTURE IN THE BASIC GENERAL EDUCATION FIRST DEGREE CHILDREN EMOTIONAL DEVELOPMENT OF EDUCATIONAL SCHOOL ATTACHED TO THE LOJA UNIVERSITY, LOJA CITY, PERIOD 2013 – 2014. PROPOSITIONAL GUIDELINES The general objective was: To analyze the incidence of Family Basic General Education First Degree Children Emotional Development Of Educational School Attached To The Loja, University Loja, City, Period 2013 – 2014. The methods used were the same: Scientist, Analytical, Synthetic, Inductive - Deductive, Descriptive and Statistical Model. Techniques and instruments used were : a survey of parents of children in the First Degree General Education Basic Education Unit Attached to the National University of Loja, Loja city , to identify the Family Structure ; and Development Program of Emotional Intelligence applied to children to assess Emotional Development . In the implementation of the parents survey concludes that: 74% of parents surveyed said that their two-parent nuclear family; 22% single-parent nuclear family; 4% extensive or composite family. From the results of the Program of Trade Intelligence concluded that: 90% children from the First Degree General Education of Basic Education Unit Attached to Loja National University, have an Emotional development of 90% Positive, and 10 % negative.